Pulmonary Function Testing in Elderly Patients Treated for a Myasthenia Gravis Exacerbation. (April 2019) - van Gaal, Stephen C.; English, Shane W.; Bourque, Pierre R. J.; Zwicker, Jocelyn C.
Background and Purpose: Pulmonary function testing is a standard part of care for patients admitted to hospital with a myasthenia gravis exacerbation. It may inform clinicians' decisions to intubate patients. It is known that pulmonary function declines with age in healthy adults. We studied the effect of age on pulmonary function and serious respiratory events, including intubation, in patients admitted to hospital for a myasthenia gravis exacerbation. Methods: Single center, retrospective cohort of consecutive patients treated for a myasthenia gravis exacerbation. Demographics, pulmonary function tests (PFTs), and respiratory events requiring intubation or emergency respiratory therapy were recorded for each encounter. Relationship of PFTs to age was analyzed using age as a continuous and as a dichotomous (cut-value 70 years) variable. Results: Forty-nine encounters from 39 patients were included. Slow vital capacity (SVC) was negatively correlated with age ( R 0.46, P value .002). Maximum inspiratory pressure (MIP) and SVC were significantly reduced in elderly versus nonelderly patients (MIP-20.0 vs −30.0 cm H2 O, P value .004; SVC 16.5 vs 23.4 mL/kg, P value .013). The incidence of respiratory events did not significantly differ between elderly and nonelderly patients (χ 2 P value .08). Conclusions: In patients treated for a myasthenia gravis exacerbation, pulmonary function values are significantly reduced in elderly patients compared to nonelderly patients. Despite very low SVC and MIP values most elderly patients do not require intubation however they do require intensive monitoring for serious respiratory complications.